Non-suicidal self-injury in adolescents with mood disorders and the roles of self-compassion and emotional regulation - Liu, Jing; Li, Jia-ting; Zhou, Man; Liu, Hui-feng; Fan, Yang-yang; Mi, Si; Tang, Yi-lang (Frontiers in Psychiatry, 2023)
Objective: We aimed to investigate the characteristics and psychological mechanism of non-suicidal self-injury (NSSI) in adolescents with mood disorders. We examined how self-compassion and emotional regulation affected NSSI and tested the mediating role of self-compassion in the link between emotional regulation and NSSI.We recruited outpatient and inpatient adolescent patients with bipolar and related disorders or depressive disorders (DSM-5), with a focus on NSSI. We also recruited healthy controls from the community. We collected demographic and clinical data. The Adolescent Self-injury Questionnaire, Self-compassion Scale (SCS), and Emotion Regulation Questionnaire (ERQ) were used to assess the frequency and severity of NSSI, level of self-compassion, and emotional regulation.In total, we recruited 248 adolescent patients with mood disorders (N=196 with NSSI, and 52 without NSSI) and 212 healthy controls. NSSI was significantly associated with the female sex, lower levels of education and less use of cognitive reappraisal strategies, lower levels of self-warmth, and higher levels of self-coldness. Multivariate analysis of variance showed that there were significant differences in the scores of ERQ, cognitive reassessment score, and the scores of SCS among the three 删除了: This study This is a provisional file, not the final typeset article groups, but no statistical differences in expressive suppression score among the three groups. Selfwarmth had a mediating effect between cognitive reappraisal and NSSI behavior.NSSI is prevalent among adolescent patients with mood disorders in clinical settings, especially among girls and those with lower levels of education and less cognitive reappraisal strategies. More clinical attention is needed. Self-compassion and its factors may mediate the association between emotional regulation and NSSI. Clinical implications and future research directions were discussed.